3-3(x-6)=5x+12

Simple and best practice solution for 3-3(x-6)=5x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-3(x-6)=5x+12 equation:


Simplifying
3 + -3(x + -6) = 5x + 12

Reorder the terms:
3 + -3(-6 + x) = 5x + 12
3 + (-6 * -3 + x * -3) = 5x + 12
3 + (18 + -3x) = 5x + 12

Combine like terms: 3 + 18 = 21
21 + -3x = 5x + 12

Reorder the terms:
21 + -3x = 12 + 5x

Solving
21 + -3x = 12 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
21 + -3x + -5x = 12 + 5x + -5x

Combine like terms: -3x + -5x = -8x
21 + -8x = 12 + 5x + -5x

Combine like terms: 5x + -5x = 0
21 + -8x = 12 + 0
21 + -8x = 12

Add '-21' to each side of the equation.
21 + -21 + -8x = 12 + -21

Combine like terms: 21 + -21 = 0
0 + -8x = 12 + -21
-8x = 12 + -21

Combine like terms: 12 + -21 = -9
-8x = -9

Divide each side by '-8'.
x = 1.125

Simplifying
x = 1.125

See similar equations:

| 4y-21=-35+6y | | 15.50=26-79 | | 10x-45=3x-45 | | 6s-11=-23+9s | | 2x+13=10x+5 | | -17-3x=-50 | | -2v+10=2(5-v) | | x+3/2=9 | | (1-2q)-3=15 | | 435=32x+40 | | 6(3+2x)-3=63 | | -5x-16=-7+26 | | x+1/2=9 | | 2(3+6x)-1=41 | | 9+15z-7=9z+34-2z | | 9p+2.6=7.8+8p | | 7/1000= | | -42-4c=2c | | 9(4x-1)=3(12x+3) | | 56(7x-3)+78=6(7-3x)-78 | | 9/50= | | 9+4r-7=6r+14-4r | | 17w-2=15w | | 16(x^2+11x+36)=0 | | 1.2=0.4y | | 5t-11=2t-5 | | -5y+5=-9y | | -17w-2=15w | | 0.7*2.4+16+4*2.4=27.28 | | x+3=2/9 | | 11/20= | | 2m+9m=33 |

Equations solver categories